The Narrowing of Self as Perceived by People in the Early Stages of Dementia—The Second Report - Hiromi Toki; Masako Tai; Sayumi Nojima (Florence Nightingale Journal of Nursing)
Aim: The purpose of this study is to shed light on the sense of self that occurs amongst those who have been diagnosed with the early stages of dementia, where the individual attempts narrowing their world.